Histological and Hormonal Alterations in the Ovaries of Rats Treated with Estradiol and Corn Oil - Dmoaa Majid, Dmoaa; Hazar; Hassan; Fatma (University of Thi-Qar Journal of agricultural research, 2025)
Increasing estrogen levels beyond the normal limit can be an indicator of a serious health problem which can be the cause of fibrosis or tumor development in the ovary tissue. In the current study, we seek to understand the mechanism of estrogen and whether the exposure of estradiol and phytoestrogens together increases the risk of developing ovarian cancer. Here, we used 32 healthy adult female rats. They were randomly divided into four groups. The first group (the control group) and the remaining groups were dosed orally with estradiol (30 micrograms/kg) and corn oil (0.5 ml) for six weeks. Our study showed a significant increase in the progesterone, estrogen, and their receptors levels within the treated groups. Further, the histological examinations indicate an increase in ovarian follicles at different stages of development and numerous mature Graafian follicles. We noticed that there were more corpora lutea and the granulosa cell layer was thicker in the treated groups compared to the control group.Taken together, our data suggested that phytoestrogens have a mechanism of action that mimics the body’s internal (endogenous) estrogens, especially in the growth and development of ovary tissue. Therefore, adopting a diet rich in plant estrogens for a long period can cause an increase in the level of internal estrogens and disrupt their function.